Granular Activated Carbon Adsorption Process for Removing Methyl tert-Butyl Ether from Groundwater - Hu, Juan; Huang, Liu-Ya; Li, Bing-Jing; Zhang, Wei; Ying, Wei-Chi (Asian Journal of Chemistry, 2012)
Methyl tert-butyl ether (MTBE), a popular organic solvent and gasoline additive, has become a common groundwater pollutant. Extensive batch adsorption isotherm experiments and continuous flow breakthrough experiments were conducted to identify the most attractive granular activated carbon (GAC) and to determine the effects of important factors governing the GAC treatment effectiveness. The organic constituents of the test solution reduced the GAC's capacity for MTBE in pure water and that the reduction was dependent on both the solution composition and the GAC's pore structure. GAC's phenol number is a useful indicator of its adsorptive capacity for MTBE. MTBE breakthrough data confirmed the relative isotherm capacities and illustrated the better capacity utilization of using two serial adsorbers relative to a larger adsorber holding the combined amount of GAC. The environmental friendly bamboo JHBG1 was the most cost effective of 7 GACs studied. The GAC adsorption treatment is practical for removing a small quantity of MTBE from groundwater; biodegradation of MTBE in the adsorber will enable its long term service without periodic GAC replacement.